2004
DOI: 10.7213/reb.v26i55.21640
|View full text |Cite
|
Sign up to set email alerts
|

Peixes Pelágicos Da Lagoa Rodrigo De Freitas, Rio De Janeiro, Brasil

Abstract: O objetivo desse estudo é caracterizar a composição da ictiofauna pelágica, a distribuição espacial/sazonal e a abundância relativa na Lagoa Rodrigo de Freitas. As coletas foram realizadas de março de 1991 a abril de 2004 em quatro áreas, com o auxílio de tarrafas, arrasto-de-praia, puçá e rede-de- espera. No laboratório, o material foi identificado, pesado e medido. Foram realizadas 103 coletas, sendo capturados 113.109 espécimes, correspondendo a 65 espécies, das quais 104.790 espécimes foram pelágicas, corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Fish assemblages of the Cabiiinas and other coastal lagoons in Rio de Janeiro state, such as Marapendi (Andreata, Saad, and Barbieri, 1989), Tijuca (Andreata et al, 1990), Iquipari (Lima et al, 2001), Rodrigo de Freitas lagoons (Andreata et al, 2002) and Imboassica (Saad, Beaumord, and Caramaschi, 2002) have suffered reduction in diversity and species richness, especially because of the loss of contact with the sea or because of poor communication with the adjacent ocean. The lack of renewal of marine dependent species that temporarily colonize these lagoons favoured the dominance of an ichthyofauna with freshwater or coastal lagoon resident species characteristics, which are adapted to lenthic environments and complete their entire life cycle in coastal lagoons.…”
Section: Temporal Variation Of Fishmentioning
confidence: 99%
“…Fish assemblages of the Cabiiinas and other coastal lagoons in Rio de Janeiro state, such as Marapendi (Andreata, Saad, and Barbieri, 1989), Tijuca (Andreata et al, 1990), Iquipari (Lima et al, 2001), Rodrigo de Freitas lagoons (Andreata et al, 2002) and Imboassica (Saad, Beaumord, and Caramaschi, 2002) have suffered reduction in diversity and species richness, especially because of the loss of contact with the sea or because of poor communication with the adjacent ocean. The lack of renewal of marine dependent species that temporarily colonize these lagoons favoured the dominance of an ichthyofauna with freshwater or coastal lagoon resident species characteristics, which are adapted to lenthic environments and complete their entire life cycle in coastal lagoons.…”
Section: Temporal Variation Of Fishmentioning
confidence: 99%
“…ANDREATA et al (2002ANDREATA et al ( , 2004 reported 63 fish species in the lagoon, 54 of which were marine and 9 were freshwater species. According to these authors, the lagoon plays a major role in marine life by attracting a large diversity of marine fish; however, the lagoon freshwater species do play an important role with respect to the total number of captured species.…”
Section: Zooplankton Communitymentioning
confidence: 99%
“…In this sense, the deposits of The new locality record for C. jorgei of the current study, the Rodrigo de Freitas lagoon, is characterized by being isolated from the sea by the Ipanema and Leblon beaches, but it has a connection with the sea through the Jardim de Alah channel (Andreata 2012). This lagoon has frequent problems associated with pollution, which result in deterioration in water quality, gas emissions, siltation and sh mortality; however, shing activities and trade are regular and economically important for the municipalities of Rio de Janeiro (Barroso et al, 2000;Andreata et al 2002). These observations reveal that, despite the expected absence or low prevalence of parasites with heteroxenic cycles in polluted environments, C. jorgei and possibly other Contracaecum spp.…”
Section: Resultsmentioning
confidence: 99%